2010
DOI: 10.1186/1750-1326-5-30
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Aβ treatment leads to impairment in the ability of primary cortical neurons to maintain K+ and Ca2+ homeostasis

Abstract: BackgroundAlzheimer's disease (AD) is a progressive neurodegenerative disease, characterised by the formation of insoluble amyloidogenic plaques and neurofibrillary tangles. Beta amyloid (Aβ) peptide is one of the main constituents in Aβ plaques, and is thought to be a primary causative agent in AD. Neurons are likely to be exposed to chronic, sublethal doses of Aβ over an extended time during the pathogenesis of AD, however most studies published to date using in vitro models have focussed on acute studies. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Although, it is possible that the baclofen treatment masked the toxic effect of Aβ by an unrelated mechanism, taken together with our other data, the correlation between baclofen-induced down-regulation of GIRK channel activity and reduced Aβ-toxicity is consistent with a causal relationship. Potassium dysregulation is a feature of Alzheimer's disease brain tissue (Roberts et al, 2016 ), and similar to our findings, others have shown that potassium efflux from cortical neurons can be promoted by Aβ, and that this efflux is required to cause subsequent degeneration, although the mechanism remains unclear (Yu et al, 1998 ; Shabala et al, 2010 ). Our data indicate that Aβ 42 treatment causes sufficient potassium to leave the cell to reduce the intracellular potassium concentration to approximately half (80 mM), which in turn is permissive for the apoptosome to assemble and caspases to be activated, a finding that is consistent with previous reports (Cain et al, 2001 ; Coulson et al, 2008 ).…”
Section: Discussionsupporting
confidence: 89%
“…Although, it is possible that the baclofen treatment masked the toxic effect of Aβ by an unrelated mechanism, taken together with our other data, the correlation between baclofen-induced down-regulation of GIRK channel activity and reduced Aβ-toxicity is consistent with a causal relationship. Potassium dysregulation is a feature of Alzheimer's disease brain tissue (Roberts et al, 2016 ), and similar to our findings, others have shown that potassium efflux from cortical neurons can be promoted by Aβ, and that this efflux is required to cause subsequent degeneration, although the mechanism remains unclear (Yu et al, 1998 ; Shabala et al, 2010 ). Our data indicate that Aβ 42 treatment causes sufficient potassium to leave the cell to reduce the intracellular potassium concentration to approximately half (80 mM), which in turn is permissive for the apoptosome to assemble and caspases to be activated, a finding that is consistent with previous reports (Cain et al, 2001 ; Coulson et al, 2008 ).…”
Section: Discussionsupporting
confidence: 89%
“…This dose regimen was shown to produce a significant accumulation of Aβ in Z310 cells in our previous studies (Behl et al, 2009a, Behl et al, 2009b) and in vitro toxicity studies (Shabala et al, 2010). Aβ concentrations in outer chamber were gradually increased from 0 into 0.28±0.06 ng/ml at 1 hr and 4.2±0.96 ng/ml at 3 hrs following treatments.…”
Section: Resultsmentioning
confidence: 83%
“…Complete experimental procedure of microelectrode ion flux estimation (MIFF) has been processed by a modified procedures according to the previously reports (Shabala et al, 2010). Cortical neurons for the MIFE detections were cultured for 6 days at 5× 10 5 cells/well on coverslips coated with poly-L-lysine.…”
Section: Ion-selective Flux Measurementsmentioning
confidence: 99%